The effect of kids yoga practices on attention levels and frontal EEG theta/beta ratio - Baba Kaya, Hande; Görün, Levent; Alper, Rumeysa; Akpınar, Selahattin; Koç, Mustafa; Çelen, Aylin; Eroğlu Eskicioğlu, Yeşer; Pepe, Şirin (Frontiers in Psychology, 2025)
IntroductionThe aim of this study was to investigate the effects of children’s yoga practices on attention levels and frontal EEG theta/beta power ratios in young athletes.MethodsThis research was conducted using a triple regulation design from mixed research methods. The participants were 20 female midi volleyball players (Mean = 11.45; SD = 0.49) with 3 years of volleyball experience from Düzce Volleyball Sports Club. They were randomly assigned to experimental and control groups. The experimental group participated in 24 sessions of children’s yoga, each lasting 40 minutes, at least 3 days per week for 8 weeks, including asanas (postures) and pranayama (breathing) techniques designed for children. The control group did not receive any intervention. Quantitative data were collected using the d2 attention test and Nexus 10 Mk II EEG device, while qualitative data were obtained through semi-structured interviews. Two-way repeated measures ANOVA was applied to the quantitative data, and thematic analysis was used for the qualitative data.ResultsThe d2 attention test results indicated significant improvements in TN-E scores for the experimental group compared to the control group (Wilks’ λ = 0.226, F(1,18) = 61.74, p < 0.05). EEG analysis showed significant effects of yoga on frontal theta/beta power ratios: Fz (Wilks’ λ = 0.987, F(1,18) = 19.32, p < 0.05, η2 = 0.518), F7 (Wilks’ λ = 0.692, F(1,18) = 8.01, p < 0.05, η2 = 0.308), and F8 (Wilks’ λ = 0.605, F(1,18) = 11.74, p < 0.05, η2 = 0.395). Qualitative findings indicated that coaches observed higher focus and better responses to strategies among athletes in the yoga group.DiscussionThese findings suggest that children’s yoga practices have a significant impact on improving attention levels and frontal EEG theta/beta ratios, contributing to enhanced neurophysiological indicators of attention. Coaches also reported improvements in concentration and performance-related behaviors. Therefore, children’s yoga practices may be considered as a supportive training tool to enhance young athletes’ performance.